2002
DOI: 10.21608/ejabf.2002.1745
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Effects of Copper Sulfate, Malathion and Paraquat on Protein Pattern of Oreochromis Niloticus

Abstract: T he present study deals with the effect of some water pollutants; copper sulfare as a fungicide, malathion as an insecticide and paraquat as a herbicide, on ;:' _rum total protein serum albumin and globulin. Furthermore, protrrinogram of blood serum niloticus in Oreochromis was done using electrophoresis. It was found that the control fish have nine serum protein fractions. The exposure offish to the examined pollutants induced a disappearance of some fractions and consequently changes of relative mobility an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…In the present study, the protein electrophoresis shows a large difference between reference and contaminated samples. This agrees with Sharaf-El-Deen & Abdel-Hamid (2002), who conclude that this difference is attributed to the production of a new DNA sequence, which synthesizes new protein bands. The study under review also agrees with several studies which report that the disappearance of bands is proved under the action of pollution (Muthukumaravel et al 2007;Osman et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the protein electrophoresis shows a large difference between reference and contaminated samples. This agrees with Sharaf-El-Deen & Abdel-Hamid (2002), who conclude that this difference is attributed to the production of a new DNA sequence, which synthesizes new protein bands. The study under review also agrees with several studies which report that the disappearance of bands is proved under the action of pollution (Muthukumaravel et al 2007;Osman et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…These parameters are closely related to the response of the animal to the environment, an indication that the environment where fish lives could exert some influence on the blood characteristics (Fernandes & Mazon 2003). As well as haematological parameters, also the determination of protein content in blood plasma is a good indicator to detect intra-and inter-specific variation among species, identify populations, and for investigation of ecological stress, physiological homeostasis and aquatic pollution (Sharaf-El-Deen & Abdel-Hamid 2002). Serum proteins are very complex and are involved in a wide range of physiological functions in both healthy and disease states, which is why they play a role of great importance for zoologists, enzymologists, immunologists and toxicologists.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported that Cu induce deleterious effects on physiological, haematological and histological changes in different fish species (Sharaf-Eldeen and Abdel-Hameid 2002;AbdelTawwab et al 2007;Carvalho and Fernandes 2008;Oliveira et al 2008). The haematological variables were frequently used as fast indicators of fish response to environmental stressors (Webener et al 1992;Shah 2006).…”
Section: Introductionmentioning
confidence: 99%